PENYELESAIAN SENGKETA PERKAWINAN MELALUI PERADILAN ADAT DI KECAMATAN TANJUNG KEMUNING - Marpensory, Marpensory (UIN Fatmawati Sukarno Bengkulu, 2017)
Marriage disputing that led to send a letter of divorce to the wife, so traditional authorities do mediation session for the peace of process, traditional authorities seek to reconcile the husband and wife. When the peace can not be reached, so that the status of husband and wife officially divorced, then customs will hold treaty / agreement with a content that when the two sides will conduct a marriage with another person, a husband or wife will not demand to the authorities, the letter of the agreement signed on the stamp 6000 is known by the traditional authorities. There are three issues that must be studied in this thesis, namely: (1) How to solve the disputing processes conducted by the customary court ?, (2) How is the effectiveness of traditional justice in reducing the number of divorce? (3) How is the legality of the customary verdict against divorce case ?. The purpose of this study was to determine how to resolve the dispute marriages customary justice, determine the effectiveness of traditional justice in reducing the divorce rate and the legality of the decision Knowing customary in divorce cases in the district of TanjungKemuning. In this study, using field research, with a qualitative descriptive research. To collect the data studied using interviews, literature review and documentation. From these results it can be concluded that there were 40 cases of disputes that separated in villages in district of tanjungkemuning as many as 24 cases successfully reconciled by traditional authorities in the district of tanjungkemuning. The process is carried out emphasizes the nature of kinship, not entailing excessive cost so the effective result that households back in harmony. The legality of the decision of customs that promote the agreement of both sides of husband and wife to the dispute are legal standing when tested with the theory of legal certainty of the decision does not have binding legal force because according to Law No. 1 of 74 Article 39, paragraph 1 says “Divorce can only be done in courtroom after the court concerned to try and not managed to reconcile the two sides Similarly, the Islamic Law Compilation (KHI) article 155 it is said that” “Divorce can only be done in front of the Religious court after the Religious courts are tried and did not succeed to reconcile both sides.”